2022
DOI: 10.1111/irv.13003
|View full text |Cite
|
Sign up to set email alerts
|

Modelled estimates of hospitalisations attributable to respiratory syncytial virus and influenza in Australia, 2009–2017

Abstract: Background Respiratory syncytial virus (RSV) and influenza are important causes of disease in children and adults. In Australia, information on the burden of RSV in adults is particularly limited. Methods We used time series analysis to estimate respiratory, acute respiratory infection, pneumonia and influenza, and bronchiolitis hospitalisations attributable to RSV and influenza in Australia during 2009 through 2017. RSV and influenza‐coded hospitalisations in <5‐year‐olds were used as proxies for relative wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Our study used both modelled (influenza‐associated) and observed (influenza‐coded) hospitalisation estimates. Reliance on diagnosis codes only can underestimate influenza‐associated hospitalisations [2, 3]. This can occur because not all patients are tested for influenza and some positive test results are not recorded [2, 37].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study used both modelled (influenza‐associated) and observed (influenza‐coded) hospitalisation estimates. Reliance on diagnosis codes only can underestimate influenza‐associated hospitalisations [2, 3]. This can occur because not all patients are tested for influenza and some positive test results are not recorded [2, 37].…”
Section: Discussionmentioning
confidence: 99%
“…It may be that as the accessibility, frequency and rapidity of testing have increased over time, ICD codes are now able to provide more sensitive estimates of influenza‐associated hospitalisations. On the other hand, including more diagnosis fields increases the risk of admissions with incidental infection being included [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations